The evolution of the machine : - Calder, Ritchie (American Heritage Pub. Co.; book trade and institutional distribution by Van Nostrand, 1968)
Contents: So writes author Ritchie Calder in introducing the machine, which is the main character of this lively work and a vital and inescapable part of all our lives